Blastococcus tunisiensis sp. nov., isolated from limestone collected in Tunisia. Issue 6 (23rd June 2022) - Louati, Moussa; Hezbri, Karima; Montero-Calasanz, Maria del Carmen; Rohde, Manfred; Göker, Markus; Ghodhbane-Gtari, Faten; Klenk, Hans-Peter; Nouioui, Imen; Gtari, Maher
Abstract : A new actinobacterium strain, designated BMG 823 T, was isolated from a limestone sample collected in Tunisia. Its taxonomic position was scrutinized using a polyphasic approach. Colonies of strain BMG 823 T were pink orange-coloured, regular and had a moist surface. Cells are Gram-stain-positive, catalase-negative and oxidase-negative. The strain grew at pH 5.5–9, 10–40 °C and in presence of up to 4 % NaCl (w/v). Chemotaxonomically, strain BMG 823 T was characterized by cell-wall type III containing meso -diaminopimelic acid as diamino acid, glucose, ribose and rhamnose as whole-cell sugars, MK-9(H4 ) as predominant menaquinone, and phosphatidylcholine, diphosphadidylglycerol, phosphatidethanolamine, phosphatidylcholine, phosphatidylinositol, unidentified glycolipid, unidentified aminophospholipids and unidentified glycophospholipid as major polar lipids. The fatty acid profile consisted of iso-C16 : 0 and iso-C17 : 1 ω 9. Phylogenetic trees based on 16S rRNA gene and genome sequences placed strain BMG 823 T within the genus Blastococcus and separated it from all type strains of validly published species. Comparison of 16S rRNA gene sequence similarity, digital DNA–DNA hybridization and average nucleotide identity indicated that strain BMG 823 T was most closely related to Blastococcus litoris DSM 106127 T and Blastococcus colisei BMG 822 T with pairwise values well below the species differentiation thresholds. The distinct phenotypic and genotypic features of strain BMG 823 T (=DSM 46838 T =CECT 8881 T ) within the genus Blastococcus warrant its recognition as the type strain for the new species for which we propose the name Blastococcus tunisiensis sp. nov.